Structural and optical properties of ZnO nanostructures on nanostructured porous silicon by thermal chemical vapour deposition method / Hartini Ahmad Rafaie - Ahmad Rafaie, Hartini (2009)
Zinc oxide (ZnO) is a direct wide band gap semiconductor material of 3.3 eV and has a large excitation binding energy of 60 meV. The non-toxicity, thermally stable and the wide availability of its component raw materials give additional advantages for ZnO to be used in many applications. In this thesis, the structural and optical properties of ZnO nanostructures have been studied. Thermal chemical vapor deposition method and basic characterization using Scanning Electron Microscopy (SEM), X-ray diffraction (XRD) technique and photoluminescence (PL) measurement become a key idea of this thesis. Two stages preparation was involved are preparation of nanostructured porous silicon (NPSi) substrate and preparation of ZnO nanostructures. A number of ZnO nanostructures samples have been prepared by dividing into four set of experiment that is ZnO deposited on NPSi substrate, on Au-coated NPSi substrate, on Si substrate and on Au-coated Si substrate at various deposition temperatures. It can be observed that NPSi20 subtrate is the best sample to act as a substrate for ZnO preparation as it surface structure is uniform and thickness is better compared to other samples.